Right heart failure after left ventricular assist device: From mechanisms to treatments - Bravo, Claudio A.; Navarro, Andrew G.; Dhaliwal, Karanpreet K.; Khorsandi, Maziar; Keenan, Jeffrey E.; Mudigonda, Parvathi; O'Brien, Kevin D.; Mahr, Claudius (Frontiers in Cardiovascular Medicine, 2022)
Left ventricular assist device (LVAD) therapy is a lifesaving option for patients with medical therapy-refractory advanced heart failure. Depending on the definition, 5-44% of people supported with an LVAD develop right heart failure (RHF), which is associ-ated with worse outcomes. The mechanisms related to RHF include patient, surgical, and hemodynamic factors. Despite significant progress in understanding the roles of these factors and improvements in surgical techniques and LVAD technology, this complication is still a substantial cause of morbidity and mortality among LVAD pa-tients. Additionally, specific medical therapies for this complication still are lacking, leaving cardiac transplantation or supportive management as the only options for LVAD patients who develop RHF. While significant effort has been made to create al-gorithms aimed at stratifying risk for RHF in patients undergoing LVAD implantation, the predictive value of these algorithms has been limited, especially when attempts at external validation have been undertaken. Perhaps one of the reasons for poor per-formance in external validation is related to differing definitions of RHF in external co-horts. Additionally, most research in this field has focused on RHF occurring in the ear-ly phase (i.e., <1 month) post LVAD implantation. However, there is emerging recogni-tion of late-onset RHF (i.e., > 1 month post-surgery) as a significant cause of morbidity and mortality. Late-onset RHF, which likely has a unique physiology and pathogenic mechanisms, remains poorly characterized. In this review of the literature, we will de-scribe the unique right ventricular physiology and changes elicited by LVADs that might cause both early- and late-onset RHF. Finally, we will analyze the currently available treatments for RHF, including mechanical circulatory support options and medical therapies.